Ten greatest discoveries of the 20th century in cardiovascular medicine - van der Wall, E.E. (2004)
The Netherlands Society of Cardiology (NVVC) was founded 70 years ago on 28 April 1934. When looking back at the history of our Society on its 70th anniversary, it might be a nice opportunity to mention ten great discoveries in cardiology in the 20th century.